LIBRARIAN BEHAVIOR IN SEARCHING INFORMATION AT SRIWIJAYA UNIVERSITY LIBRARY 2024 (Case Study in Sriwijaya University Bukit Reading Room) - Beta Ria Febrianti; Novita Vitriana; Jaswarman Putra; Yuni Astuti Pasmawaty (Progam Studi Ilmu Perpustakaan UIN Sumatera Utara Medan, 2025)
The purpose of this study was to determine the behavior of library users in searching for information and what obstacles were found in searching for information faced by library users at the Sriwijaya University Library in 2024 (Case Study in the Sriwijaya University Bukit Reading Room). The method used in this study is quantitative descriptive. The subjects of the study were 100 library users who visited the Sriwijaya University Bukit reading room, obtained using the Slovin formula. The sampling technique used was the Purposive Sampling technique. Data collection techniques used questionnaires and observations. The results of this study are the information seeking behavior of students in meeting information needs in the Sriwijaya University Bukit reading room from the application of Wilson and Ellis' theory, namely for an average starting of 3.03, at the chaining stage of 3.154, at extracting of 2.722, the verifying stage of 3.32 and the ending stage of 3.228. At the verifying stage, it is on a very positive scale. Meanwhile, for the starting, chaining, extracting and ending stages are on a positive scale. The obstacles faced by librarians are the lack of the latest printed book collections and the unstable internet network in the Sriwijaya University Bukit reading room when many librarians visit.